Politik Uang Pada Pemilihan Umum - Vandita, Lalu Yoga; Saputra, Hirmayadi (LPPM Institut Pendidikan Nusantara Global, 2024)
Money politics has always been a hot topic of discussion for various groups in every moment of discussion by political observers, academics, election activists, anti-corruption activists, at various events organized by election organizing institutions, in various activities carried out by organizations, both mass organizations or non-governmental organizations, even to community discussions, especially around the time of the election or regional election.The behavior of society towards the current election is still less concerned about an honest and fair election, this can be seen from the phenomenon of money politics that occurs in our society. This research method uses a descriptive method with a qualitative approach. Examining what actually happened